1980
DOI: 10.1159/000214376
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of PGI<sub>2</sub> Synthetase within the Arterial Wall by 15-Hydroperoxyarachidonic Acid Enhances Local White Platelet Thrombosis

Abstract: Prostaglandins play an important role in platelet-vessel wall interaction. The inhibition of PGI2 synthetase by 15-hydroperoxyarachidonic acid (15-HPAA) results in an enhancement of local thrombus formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It was demonstrated in previous publications that T [3] and 15-hydroperoxyarachidonic acid [4], both inhibitors of the PGI2 synthetase, markedly enhanced thrombosis while the in hibitors of the cyclooxygenase [1,2] activity with compounds such as ASA, indomethacin [1] or flurbiprofen [2] significantly decreased locally induced platelet thrombosis. These results suggested that one of the determining factors in the generation of thrombus forma tion could well be the ratio of PGG2-PGH2 to Table I T AA + T T AA + T T AA + T T AA + T 1 44 31 44 60 230 210 10 8 70 70 2 16 11 54 64 570 875 9 8 185 280 3 11 19 81 94 163 255 5 7 55 70 4 25 18 61 78 300 375 5 8 162 125 5 27 18 64 93 210 407 10 11 90 139 6 20 13 80 89 580 527 10 8 1,033 1,...…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It was demonstrated in previous publications that T [3] and 15-hydroperoxyarachidonic acid [4], both inhibitors of the PGI2 synthetase, markedly enhanced thrombosis while the in hibitors of the cyclooxygenase [1,2] activity with compounds such as ASA, indomethacin [1] or flurbiprofen [2] significantly decreased locally induced platelet thrombosis. These results suggested that one of the determining factors in the generation of thrombus forma tion could well be the ratio of PGG2-PGH2 to Table I T AA + T T AA + T T AA + T T AA + T 1 44 31 44 60 230 210 10 8 70 70 2 16 11 54 64 570 875 9 8 185 280 3 11 19 81 94 163 255 5 7 55 70 4 25 18 61 78 300 375 5 8 162 125 5 27 18 64 93 210 407 10 11 90 139 6 20 13 80 89 580 527 10 8 1,033 1,...…”
Section: Discussionmentioning
confidence: 95%
“…In previous investigations the role of the prostaglandin biochemical pathway in the generation of white platelet thrombosis was clearly established [1][2][3][4], Evidence was ad duced that the adhesion of platelets onto the intimal structures followed by thrombus for mation was determined mainly by the ratio of the cyclic endoperoxides (PGG2-PGH2) to prostacyclin (PGI2) present in the vessel wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because prostacyclin is irreversibly inhibited by low concentrations of peroxynitrite [224] and certain products of lipid peroxidation, including oxidized LDL [225,226]. …”
Section: Introductionmentioning
confidence: 99%
“…These phenomena are evidenced by elec tronically processed microprojection [6] and ultrastructural control [7], Topical superfusion with inhibitors of cy clooxygenase such as acetylsalicylic acid (ASA), indomethacin, and flurbiprofen [1,2] results in an immediate and statistically sig nificant decrease of the ADP-induced throm botic phenomenon; conversely, superfusion with inhibitors of PGI2 synthetase such as tranylcypromine [3] and 15-hydroperoxyara-chidonic acid [4] markedly enhances throm bosis. These compounds interfere with the prostaglandin metabolism of the cells of the vessel wall, evidently also those surrounding the small area of desendothelialization.…”
Section: Introductionmentioning
confidence: 99%